Ensino de história e pertencimentos nacionais : narrativas de alguns jovens sergipanos sobre a história do Brasil - Santana, Crislane Dias (2019)
This research has objectified analyzing the produced narratives by young people about the history of Brazil and to identify possible national belongings accrued from scholastic and extra scholastic historical knowledge from these students. The porpoise of investigating narratives about belongings was linked to a research in web also developed together with another national institutions (UFRGS, UEPG, UFS, and the IFG), denominated “The country and the world in few words: narratives of young people about belongings – implications to the history teaching”. We consider that the narratives about the national belongings are permeated for knowledge that circles socially and are part of the processes of teaching and learning history. In this sense interest to us know which are these historical knowledge about Brazil narrated by youth of Sergipe in a age range between 12 and 16 years old. As research instruments, we prioritize the application of questionnaire with open questions (two), that were accomplished in two public schools (A and B). The analysis was developed from the first question about the history of your country and theoretically anchored in some authors from the Didactic of the History area, that we understand as an field of study that allows us to reflect the teaching and learning of History. In this aspect, the discussions in this field, allowed us to comprehend the building of the identity and citizenship as concepts that are developed on the History Teaching, but does not restrict to it. The construction to the citizenship goes through contents and practices that potentialize the comprehension of the society on the present, therefore, it is an essential aspect on the discussions that involve the Didactic of the History. In this dissertation, the narratives about Brazilian History, elaborated by the young people from Sergipe that participated of the sample privilege the founding Event; the History with the founding violence ; the Relation between past and present (subdivided in two): problematic present and satisfactory and the Relation of national belonging. The results make possible reflect that even though externalize a comprehension about the past of the country they not always establish a feeling of belonging in relation of some historical facts and much less indentified themselves with female historical personalities, black and indigenous people that also built/build the history of Brazil. We also observe that they relate events from the past with the present, in a linear way and not linear way and put in evidence knowledge that circles socially.